The Megaloptera (Insecta) of Tocantins State, Brazil - de Andrade, Iury Cesar Pires; Fernandes, André Silva; Krolow, Tiago Kütter (Zootaxa, 2020)
Megaloptera is a small order of conspicuous holometabolous insects with 397 species and 35 genera distributed worldwide. The order comprises two extant families, the Sialidae (8 genera and 83 species) and the Corydalidae (27 genera and 314 species), both with aquatic larvae, wherea eggs, pupae, and adults are terrestrial (Rivera-Gasperín et al. 2019). Three Corydalidae genera are known from Brazil: Corydalus Latreille, 1802 (11 species), Chloronia Banks, 1908 (4 species) and the monospecific Puri Cardoso-Costa, 2013 (Cardoso-Costa et al. 2013; Rafael & Câmara 2020). Whereas, for the Sialidae, only the genus Ilyobius Enderlein, 1910 (3 species) has been found to occur in Brazil (Liu et al. 2015; Rafael & Câmara 2020, as ProtosialisVan der Wheele, 1909).